Microbial inactivation by ohmic heating : literature review and influence of different process variables - Müller, Wagner Augusto (2020)
Background The elimination of microbial cells is one of the most critical steps in food processing. Conventional heating is the application of diffusive and convective heat mechanisms and is traditionally applied to assure food safety. However, such process is also harmful to others thermosensitive compounds, compromising desirable sensorial characteristics. The large temperature gradients caused by conventional heating result in lower thermal efficiency, overheated zones and high processing times. To overcome these limitations, emergent technologies have been studied in the past years, such as ohmic heating. Scope and approach The aim of this review was to analyse the state of the art of microbial inactivation by ohmic heating. This study emphasizes comparisons of ohmic and conventional heating, as well as comparisons of ohmic heating in several distinct scenarios (such as variations in the frequency and electric field). Key findings and conclusions The literature analysis shows that the most analysed microbial species was Escherichia coli and studies dealing with fungi were less numerous comparing with studies dealing with bacteria. Concerning the lethality of conventional and ohmic heating, authors have shown that ohmic treated foods had smaller D values in various temperatures. The effect of frequency lacks of experimental data to explain the real impact of this parameter in the inactivation rate, once different authors have found divergent results. Moreover, increases in the electric field and salt content and decreases in the pH, fat and solid content have demonstrated higher heating rates and, therefore, higher inactivation rates.